Task-related oxygenation in the prefrontal cortex as a function of mask-wearing frequency: An empirical test using functional near-infrared spectroscopy - Peter A. Hall; Mohammad Nazmus Sakib; Anna Hudson; Alkarim Billawala; Geoffrey T. Fong; Hasan Ayaz (NeuroImage: Reports)
Objective: Introduction of brain hypoxia by frequent mask-wearing is a concern voiced by some who resist masking mandates. Studies have examined acute effects of one-shot mask-wearing on peripheral and cerebral oxygenation in the laboratory, but not effects of everyday mask-wearing frequencies on task-related functional activation. The objective of the current study was to examine whether frequency of mask-wearing in daily life is associated with lower task-related brain oxygenation levels, and whether the magnitude of any such effects vary by age and sex. Methods: Participants were 78 community-dwelling adults between the ages of 18 and 84 years, all of whom were vaccinated at the time of participation; 65.4% (n = 51) were female. Frequency of mask-wearing was assessed using survey questions on mask-wearing practice during an active COVID-19 mask mandate. Recordings of task-related cerebral oxygenation were taken during the completion of a simple reaction time task using 16-channel functional near-infrared spectroscopy (fNIRS). Results: The psychomotor vigilance task elicited reliable increases in cerebral oxygenation within the right mid-frontal gyrus (F(1,61.345) = 15.975, p < .001). However, there was no significant association between everyday masking frequency and performance on the psychomotor vigilance task (b = 0.059, SE = 0.092 (95% CI [-0.122, 0.241]), t = .646, p = .520), nor any association between everyday masking frequency and task-related brain oxygenation on any measurement channel (all ps < .05). Conclusions: Higher mask-wearing frequency in daily life is not associated with significantly lower levels of task-related brain oxygenation, or worse performance on a sustained attention task.